Country inequality rankings and conversion schemes - Carsten Schröder; Timm Bönke (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
Two conversion schemes may be employed for assessing income inequality from household equivalent incomes: to weight household units by size or by needs. Using data from the Luxembourg Income Study, we show the sensitivity of country inequality rankings to conversion schemes and explain the finding by means of inequality decomposition. A bootstrap approach is implemented to test for statistical significance of our results.
Keywords: D31; D63; I32; 330; inequality; equivalence scale; equivalent income; weighting; heterogeneous distribution; quasi-homogeneous distribution; inequality decomposition; Haushaltseinkommen; Einkommensverteilung; Disparitätsmaß; Schätzung; EU-Staaten